Productivity of Brachiaria decumbens in a Mixed-Culture with Pueraria phaseloides in Different Manure and Dolomite Administration Level into Suboptimal Land - Iwan Herdiawan (Indonesian Center for Animal Research and Development (ICARD), 2016)
Productivity improvement of forage in suboptimal land can be done in various ways, such as through manure and ameliorant treatment. Manure and dolomite is required by soil on suboptimal land, a combination of both can supply nutrients and improve soil biophysics. The research materials used in this study were B. decumbens, Pueraria phaseloides, manure, and dolomite. Randomized Block Design (RBD) in 3x3 factorial was applied. The dose of manure and dolomite are the first and second factors respectively, each treatment has 3 replications times. Variables measured were biomass production, dry matter production, carrying capacity, and nutrient content of forage. Results showed that the highest (P<0.05) biomass production produced by the 10 t/ha manure and 2 ton/ha dolomite treatment by 1,638.94 g/m2 compared to the other treatments, and the lowest was achieved in the control by 543.75 g/m2. Carrying capacity of B. decumbens and P. phaseloides on 10 ton/ha manure was the highest (P<0.05) by 0.08 AU compared to the other treatments. Super dolomite administration by 1 ton/ha significantly (P<0.05) produced the highest carrying capacity by amount of 0.83 AU. Manure and dolomite administration significantly (P<0.05) improved the nutritional content of B. decumbens and P. phaseloides.